Environmental and production survey methodology to estimate severity and extent of aquaculture impact in three areas of the Philippines - Palerud, Rune; Christensen, Guttorm; Legović, Tarzan; White, Patrick; Regpala, Regie (Science Diliman: A Journal of Pure and Applied Sciences, 2009)
The project “Environmental Monitoring and Modelling of Aquaculture in the Philippines” known as EMMA, was undertaken by the National Integrated Fisheries Technology Development Centre (NIFTDC) of the Bureau of Fisheries and Aquatic Resources (BFAR) and Akvaplan-niva AS of Tromsø, Norway. The project was funded by the Norwegian Agency for Development Cooperation (NORAD). This project tested survey equipment for the monitoring of aquaculture impact to the water column and sediment. Baseline surveys were undertaken as the goal of the study was to develop suitable aquaculture monitoring techniques and adapt predictive models to assist in identifying risk areas for aquaculture and allow planned development of sustainable aquaculture. Three different locations were chosen as case studies - Bolinao, Pangasinan (marine site), Dagupan (brackish water site), and Taal Lake (freshwater site). Production surveys were also undertaken to estimate production and nutrient outputs to the water bodies in order to be able to link aquaculture production with severity and extent of impacts. Different methodologies for the estimation of production were tested to find a cost effective and accurate methodology.